Collecting statistics on prisons: strengths and weaknesses of the United Nations Survey of crime trends and operations of criminal justice systems - Walmsley, Roy (Improving knowledge on crime, 2009)
The section of the United Nations Survey of Crime Trends and Operations of Criminal Justice Systems on prisons enjoys a relatively high rate of response, with an average of 47 per cent of variables completed for 2003 and 2004. However, the results of the Survey are far from being satisfactory in terms of quantity and quality. The Survey represents a unique data collection exercise through which relevant information could be collected from all Member States. It reaches the main agencies and sources of data in the criminal justice systems of Member States and, for countries providing complete responses, it allows for an analysis of the rate of attrition in the administration of justice.